SISTEMATIK REVIEW: KONTRIBUSI SISTEM MANAJEMEN DOKUMEN ELEKTRONIK TERHADAP EFEKTIVITAS PENGELOLAAN PENGETAHUAN DALAM ORGANISASI - Zaini, Rifan (STKIP Pesisir Selatan, 2025)
This study aims to gain an in-depth understanding of the contribution of the Electronic Document Management System (EDMS) to the effectiveness of knowledge management (KM) through a systematic review of scientific literature. The reviewed literature includes publications from 2019–2025 sourced from reputable databases such as Google Scholar, Scopus, ScienceDirect, and DOAJ, using inclusion criteria of articles written in Indonesian or English, published in peer-reviewed journals, and relevant to the research topic. The search process was conducted using targeted keywords combined with Boolean operators, while the literature analysis employed a narrative synthesis approach and thematic analysis to identify patterns, contradictions, and research gaps. The findings indicate that EDMS functions not only as a digital repository but also supports processes such as knowledge capture, knowledge sharing, knowledge reuse, and organizational learning through features like metadata, versioning, audit trail, real-time editing, and integration with intelligent technologies such as AI, OCR, and machine learning. The effectiveness of EDMS is influenced by user readiness, digital competence, knowledge-sharing culture, leadership, system integration, and information security management. Strategically, EDMS accelerates information access, reduces data duplication, strengthens knowledge-based decision-making, fosters innovation, and builds knowledge culture and organizational learning.